Insights on the antioxidant, antidiabetic, antiamnesic, cytotoxic, thrombolytic and antibiofilm activities of Stevia rebaudiana leaves - Noreen, Aiman; Hussain, Fatma; Shahid, Muhammad (Progress in Nutrition, 2020)
Abstract. Background and Aim: The antioxidant, antidiabetic, antiamnesic, cytotoxic, thrombolytic and biofilm inhibition activities of seven fractions (methanol, ethanol, ethyl acetate, n-hexane, n-butanol, chloroform and aqueous) of Stevia rebaudiana leaves were determined. Methodology: The antioxidant contents and activity was measured as total phenolic contents (TPC), total flavonoid contents (TFC) and free radical scavenging assays. Anti-diabetic and antiamnesic efficacies were tested in terms of glycation, alpha amylase and acetylcholinesterase inhibitions. DNA damage protection and hemolysis analysis were done to evaluate cytotoxicity. In addition thrombolytic and antibiofilm studies were performed by prescribed methods. Results: The n-butanol fraction had highest TPC, whereas, optimal TFC and antioxidant activity were observed in methanol fraction. Ethyl acetate, aqueous and chloroform fractions showed maximum antiglycation, alpha amylase inhibitory and acetylcholinesterase inhibitory activities respectively. In cytotoxic profile, hemolytic activity was in the range of 4-47%, with n-butanol being the most potent hemolytic agent. All fractions prevented DNA damage except ethanol, n-butanol and aqueous fractions. The greatest biofilm inhibition was produced by n-hexane extract for Pasteurella multocida strain and aqueous fraction for Staphylococcus aureus strain. Highest (27%) thrombolytic activity was studied in n-hexane sample. Conclusion: The current study highlighted significant biological and pharmacological activities of Stevia rebaudiana leaves that might be significant for the management and treatment of various diseases.